PROFESI KEGURUAN DALAM MENGHADAPI TANTANGAN PENDIDIKAN ABAD KE-21: TINJAUAN LITERATUR SISTEMATIS (LITERATURE SYSTEMATIC REVIEW) - Ani Sri Mulyani (Prodi PGMI STAI Sabili Bandung, 2026)
The teaching profession has a strategic role in determining the quality of education and human resource development. Social changes, information technology developments, and 21st century competency demands teachers to continuously improve their professionalism. This study aims to analyze the development of the teaching profession, teacher competence, challenges faced, and teacher professional development strategies through the Literature Systematic Review (LSR) approach. The research method was carried out by identifying, selecting, and analyzing various relevant scientific articles from national and international journals published in the range of 2019–2025. The results of the study show that teachers' professionalism is influenced by pedagogic, professional, social, and personality competencies. In addition, the digitalization of education, curriculum changes, and the demands of learning innovation are the main challenges faced by teachers today. Continuous professional development through training, certification, learning communities, and the use of digital technology is an important factor in improving the quality of the teaching profession. This study concludes that strengthening teacher competence in a sustainable manner is the key to the success of education in facing the digital transformation era.